Expression of Capacities of Future Teachers after Performing of their Pedagogical Practice and Directions of their Improvement - Barkauskaitė, Marijona; Guoba, Andrius (Pedagogika, 2015)
Education, school, teacher are considered as the main factors for the societal development in the process of the rapid changing. Thus training of the competent pedagogue is indicated as the main objective for the education strategy. For pursuit and realising of quality training it is of crucial importance to have the feedback and information from the future teachers after performing of their pedagogical practice in schools. Through self-assessment of their capacities in solving problems encountered in organizing educational process, as well as assessment of their pedagogical capacities provided by the teachers and teacher-experts, can determine and scientifically evidence directions and forms for improvement of the study process of teacher training. Data of the scientific research indicated that future teachers after self-assessment of their own capacities after performing of their pedagogical practice, already have majority of capacities required within the educational process. This was proven also by the teachers and teacher-experts. Nevertheless respondents indicated capacities and competencies that were lacking for the work with pupils. Those are: difficulties in raising concrete targets for the lesson, managing class, motivating and assessing pupils, individualising teaching process, etc. Research has also justified the need and directions for improvement of the studies and concrete subject.